2009
DOI: 10.1248/yakushi.129.741
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Collaboration between Community Pharmacies and Hospitals or Clinics in Providing Medical Treatment for Patients with Headache

Abstract: It is often noted that the collaboration of hospital-to-hospital, hospital-to-clinic and clinic-to-clinic in medical care for patients with headache is important. However, the role of community pharmacies in the medical network for consultation of patients with headache is not clear. Here, we investigated the role of pharmacists in a community pharmacy in encouraging patients with headache to undergo medical examination and elucidated their future needs using a questionnaire intended for doctors and pharmacist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…We previously reported that only verbally recommending that a patient sees a doctor by a pharmacist is ineffective, few pharmacists made written recommendations to encourage patients to see a doctor, and patient information was not shared with doctors. 11) For patients treated with prescription drugs, it has become possible for doctors and pharmacists to work together to follow up patients using TR. 6) For patients receiving treatment with OTC drugs, it is necessary to establish a follow-up system in which doctors and pharmacists work together using medication notebooks and referral letters issued by pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that only verbally recommending that a patient sees a doctor by a pharmacist is ineffective, few pharmacists made written recommendations to encourage patients to see a doctor, and patient information was not shared with doctors. 11) For patients treated with prescription drugs, it has become possible for doctors and pharmacists to work together to follow up patients using TR. 6) For patients receiving treatment with OTC drugs, it is necessary to establish a follow-up system in which doctors and pharmacists work together using medication notebooks and referral letters issued by pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, strategies may need to be devised to motivate patients to do this, as another Japanese survey of pharmacists and doctors found that 22% of pharmacists had experienced refusal by patients with headache to consult a clinic, despite the pharmacist's recommendation. 32 Community pharmacists have an important role in supporting patients with headache. This can be fostered by all key stakeholders-pharmacists, doctors, and patients-being provided with multidisciplinary opportunities to improve their MOH health literacy and to maintain an open and collaborative relationship.…”
Section: A Multidisciplinary Approachmentioning
confidence: 99%